The Influence of Telemedicine Usability, Empathy And Hospital Facility on Patient Experience in Mother and Children's Hospital - Mozart Malik Ibrahim; Anugriaty Indah Asmarany; Maria Oce Yea ST (Jurnal Ners, 2026)
The study's objective is to assess how telemedicine usability, empathy and hospital facilities affect the patient experience at a Maternity and Child Hospital (RSIA). One of the significant justifications for this research is the growing demand for healthcare services that are not only technologically up-to-date but also comfortable, effective, and humane. Quantitative explanatory method was the chosen approach of the study and its participants were 150 patients who had received treatment at RSIA. The sample was selected through purposive sampling and the data were collected via a five-point Likert-scale questionnaire. The research instrument was first validated and then the data subjected to reliability testing using Cronbach’s Alpha and classical assumption testing before multiple linear regression was applied for analysis. The study found that the three independent variable significantly and positively contributed to the patient experience. The coefficient of determination (R²) indicates that the model can explain the patient experience. From a theoretical perspective, the study supports the literature concerning the factors influencing patient experience in hospitals for mothers and children. In addition to increasing the academic literature, this study also suggests hospitals ways to enhance patient experience through optimal utilization of telemedicine, improvement of medical personnel's empathy, and hospital facilities' physical safety, comfort, and child-friendliness upgrading.